Challenges of Climate Change and the Culpability of Churches Towards an Effective Church Climate Change Action in Nigeria - Nche, George Christian; Achunike, Hilary Chukwuka; Diara, Benjamin C.; Okoli, Anuli B. (2017)
This study discussed the culpability and liturgical indifference of the church towards the challenge of climate change in Nigeria. This was done with a view to create a niche for the church in the process of climate change mitigation and adaptation in the country. Using a phenomenological method, the study revealed the following: Firstly, many rural agro-based communities along the Coastal, Savanna and Sahel ecological zones of the country are already suffering the severity of climate change impacts. Secondly, the church in Nigeria has shown little or no commitment towards the mitigation and adaptation to climate change in the country. The study therefore, challenged the church to rise to the ecological need of the time by practically intervening in the process of mitigation and adaptation to the impacts of climate change in Nigeria. This, albeit not the core mission of the church, should be an integral part of her overall mission in the country. The study suggested, among other things, two-fold intervention praxes for the church. These included Awareness Creation (AC) and Care for Climate Change Victims (CCCVs).
Keywords: the Church; Adaptation; awareness creation; Climate Change; Culpability; liturgical indifference; Mitigation